Effect of respiratory motion correction and CT-based attenuation correction on dual-gated cardiac PET image quality and quantification - Schultz, Jussi (My University, 2022)
Dual-gating reduces respiratory and cardiac motion effects but increases noise. With motion correction, motion is minimized and image quality preserved. We applied motion correction to create end-diastolic respiratory motion corrected images from dual-gated images. [18F]-fluorodeoxyglucose ([18F]-FDG) PET images of 13 subjects were reconstructed with 4 methods: non-gated, dual-gated, motion corrected, and motion corrected with 4D-CT (MoCo-4D). Image quality was evaluated using standardized uptake values, contrast ratio, signal-to-noise ratio, coefficient of variation, and contrast-to-noise ratio. Motion minimization was evaluated using myocardial wall thickness. MoCo-4D showed improvement for contrast ratio (2.83 vs. 2.76), signal-to-noise ratio (27.5 vs. 20.3) and contrast-to-noise ratio (14.5 vs. 11.1) compared to dual-gating. The uptake difference between MoCo-4D and non-gated images was non-significant (P > 0.05) for the myocardium (2.06 vs. 2.15 g/mL), but significant (P < 0.05) for the blood pool (0.80 vs. 0.86 g/mL). Non-gated images had the lowest coefficient of variation (27.3%), with significant increase for all other methods (31.6-32.5%). MoCo-4D showed smallest myocardial wall thickness (16.6 mm) with significant decrease compared to non-gated images (20.9 mm). End-diastolic respiratory motion correction and 4D-CT resulted in improved motion minimization and image quality over standard dual-gating.
Keywords: positron emission tomography, motion correction, image quality